A corpora allata farnesyl diphosphate synthase in mosquitoes displaying a metal ion dependent substrate specificity. (September 2015) - Rivera-Perez, Crisalejandra; Nyati, Pratik; Noriega, Fernando G.
Abstract: Farnesyl diphosphate synthase (FPPS) is a key enzyme in isoprenoid biosynthesis, it catalyzes the head-to-tail condensation of dimethylallyl diphosphate (DMAPP) with two molecules of isopentenyl diphosphate (IPP) to generate farnesyl diphosphate (FPP), a precursor of juvenile hormone (JH). In this study, we functionally characterized an Aedes aegypti FPPS ( Aa FPPS) expressed in the corpora allata . Aa FPPS is the only FPPS gene present in the genome of the yellow fever mosquito, it encodes a 49.6 kDa protein exhibiting all the characteristic conserved sequence domains on prenyltransferases. Aa FPPS displays its activity in the presence of metal cofactors; and the product condensation is dependent of the divalent cation. Mg 2+ ions lead to the production of FPP, while the presence of Co 2+ ions lead to geranyl diphosphate (GPP) production. In the presence of Mg 2+ the Aa FPPS affinity for allylic substrates is GPP > DMAPP > IPP. These results suggest that Aa FPPS displays "catalytic promiscuity", changing the type and ratio of products released (GPP or FPP) depending on allylic substrate concentrations and the presence of different metal cofactors. This metal ion-dependent regulatory mechanism allows a single enzyme to selectively control the metabolites it produces, thus potentially altering the flow of carbon into separate metabolic pathways. Graphical abstract: Highlights: A farnesyl diphosphate synthase is expressed in the mosquito corpora allata (CA). It synthesizes farnesyl-PP (FPP), a precursor of juvenile hormone. In the presence of Mg 2+ synthesizes FPP from isopentenyl-PP (IPP) and dimethylallyl-PP (DMAPP). In the presence of Co 2+ synthesizes geranyl-PP (GPP) from IPP and DMAPP. In the presence of an equimolar mix of metals synthesizes lower concentrations of GPP and FPP in a 1:1 proportion.